INVENTARISASI ASET DI PAROKI SANTO ALOYSIUS GONZAGA, MLATI, SLEMAN, YOGYAKARTA - Ch. Wiwik Sunarni; Bartolomeus Galih Visnhu Pradana; Endang Raino Wirjono (Yayasan Nusantara Hasana Berdikari, 2023)
Non-profit organizations are those that work for the benefit of the community without trying to turn a profit. Public inquiries about non-profit organizations' administration of donor or sponsor finances frequently center on their transparency and accountability. Financial responsibility is significant to the church because it is an organization that does not seek to make money. Non-profit organizations are anticipated to be able to give important data, including articulation of financial status, activity reports, cash flow reports, and budget summary notes, to various contributors and associations through PSAK 45 (ISAK 35). The church is a component of a non-profit organization that uses PSAK 45 (ISAK 35). According to an interview with the Mlati Parish treasurer, there are still difficulties in preparing the parish's financial reports because until now the depreciation cost of the parish's fixed assets has not been determined. The financial reports of the parish are not in compliance with KAS standards because there is no estimate for fixed asset depreciation expenses. The PKM Team of the Accounting Study Program, Faculty of Business and Economics, Universitas Atma Jaya Yogyakarta, seeing the importance of transparency in the collection and use of funds from non-profit organizations such as churches, tries to assist the Saint Aloysius Gonzaga Parish in determining the amount of depreciation expense per year, making a list of fixed assets, and creating accounting guidelines for fixed assets. The Guide to the Fixed Asset Inventory Module and the Excel File List of Fixed Assets along with depreciation calculations that can be changed at any time if needed are the outputs of this PKM.